Rolling bearing and method for manufacturing same
By forming Fe3O4 oxide films of specific thickness and microcrystalline size on the raceway surface and rolling element surface of the rolling bearing, and controlling the film formation speed, the problems of hydrogen embrittlement and insufficient durability of the oxide film are solved, and the durability of the rolling bearing is improved.
Patent Information
- Application Number
- CN202280098095.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2022-08-29
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing rolling bearings are decomposed to produce hydrogen, hydrogen invasion into the steel material, and the durability of the oxide film is insufficient, resulting in peeling problems between the raceway surface and the rolling element surface.
By forming an oxide film containing Fe3O4 on the raceway surface and the rolling element surface of the rolling bearing, the film thickness of the oxide film is controlled to be 0.6 μm or more and 2.0 μm or less, the crystal crystal size is 2.5 nm or more and 3.2 nm or less, and the film forming speed is controlled to be 0.003 μm/min or more and 0.034 μm/min or less.
An oxide film with excellent durability is achieved, which suppresses the occurrence of hydrogen embrittlement failure and improves the durability of the raceway surface and the rolling element.
Smart Images

Figure CN119546865A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rolling bearing and a method for manufacturing the same. Background Art
[0002] When a rolling bearing is used under conditions where water is mixed, sliding or electricity is applied, hydrogen is generated due to the decomposition of water or lubricant. The generated hydrogen penetrates into the steel material constituting the rolling bearing and causes hydrogen embrittlement.
[0003] Therefore, in order to prevent hydrogen embrittlement caused by hydrogen intrusion, rolling bearings having an oxide film on the surface have been proposed. For example, Patent Document 1 discloses a rolling bearing having an oxide film on the surface of a rolling member constituting the rolling bearing for suppressing the occurrence of a hydrogen generation reaction.
[0004] In addition, for rolling bearings that support a rotating shaft in a housing, creep sometimes occurs between the outer ring and the housing, which causes wear on the inner peripheral surface of the housing. Therefore, for example, Patent Document 2 discloses a rolling bearing having an inner ring, an outer ring, and a plurality of rolling elements between the inner ring and the outer ring, wherein a black oxide film having mesh-like cracks is formed on the surface of a predetermined surface of the rolling bearing.
[0005] Patent Document 2 described above describes that creep, which is likely to occur when a radial load acting on a rolling bearing is no load or a light load, can be suppressed, thereby suppressing wear of the inner peripheral surface of the housing.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-39523
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-113126 Summary of the invention
[0010] Technical problem that the invention aims to solve
[0011] However, the above-mentioned Patent Document 1 states that by setting the thickness of the oxide film on the surface of the rolling part to 0.5 μm or more, even if the oxide film is worn, the rolling part is not likely to generate a new surface, which can inhibit the hydrogen generation reaction. In addition, the above-mentioned Patent Document 2 states that by making the film thickness of the black oxide film greater than 1 μm, the durability is improved.
[0012] However, even if the thickness of the oxide film (black oxide film) is controlled within the above range, it cannot be said that the durability of the oxide film is sufficient. If the oxide film is damaged, hydrogen will penetrate into the steel and generate white structure. And, starting from this, the raceway surface and the surface of the rolling element of the rolling bearing will peel off.
[0013] The present invention has been made in view of the above problems, and its object is to provide a rolling bearing and a method for manufacturing the same, wherein the rolling bearing can obtain an oxide film with excellent durability, can suppress the occurrence of hydrogen embrittlement fracture, and thereby can improve the durability of the raceway surface and the rolling element.
[0014] Technical solutions to the problem
[0015] The inventors of the present invention have repeatedly conducted in-depth research to solve the above-mentioned problems, and found that the main damage modes of the oxide film formed on the raceway surface or rolling element of the rolling bearing are "film wear" and "film destruction", and the durability of the oxide film varies greatly depending on the processing conditions and film thickness when the oxide film is formed. It should be noted that "film wear" refers to the phenomenon that the oxide film is damaged roughly uniformly, and "film destruction" refers to the phenomenon that the oxide film is damaged unevenly, such as intra-film peeling, interface peeling, etc.
[0016] The present inventors have also found that the damage mode "film wear" varies depending on the crystallite size of Fe3O4 constituting the oxide film, and that "film destruction" varies depending on the residual stress, which is affected by the film thickness of the oxide film.
[0017] That is, the smaller the crystallite size of Fe3O4 is, the denser the film is, and the less wear of the film can be achieved, and the thinner the oxide film is, the less damage to the film can be achieved. The present invention was accomplished based on these findings.
[0018] The rolling bearing of the present invention has the structure shown in the following [1].
[0019] [1] A rolling bearing, characterized in that:
[0020] It comprises: a first raceway ring having a first raceway surface; a second raceway ring having a second raceway surface; and a plurality of rolling elements held between the first raceway surface and the second raceway surface in a freely rolling manner, wherein:
[0021] At least one of the first raceway surface, the second raceway surface, and the surface of the rolling element has an oxide film containing Fe3O4,
[0022] The oxide film has a thickness of 0.6 μm or more and 2.0 μm or less.
[0023] The crystallite size calculated from the peak attributed to the (311) plane of Fe3O4 is greater than 2.5 nm and less than 3.2 nm.
[0024] A preferred embodiment of the rolling bearing of the present invention is shown in the following structure [2].
[0025] [2] The rolling bearing according to [1], characterized in that:
[0026] The oxide film is formed on the surfaces of the first and second rolling surfaces and the surface of the rolling element.
[0027] The method for manufacturing a rolling bearing according to the present invention is as shown in the following structure [3].
[0028] [3] A method for manufacturing a rolling bearing, characterized in that:
[0029] A method for manufacturing a rolling bearing as described in [1] or [2], comprising the step of forming an oxide film containing Fe3O4 on at least one of the first raceway surface, the second raceway surface, and the surface of the rolling element,
[0030] The film formation rate of the oxide film is set to 0.003 μm / min or more and 0.034 μm / min or less.
[0031] Effects of the Invention
[0032] According to the present invention, by properly controlling the film thickness of the oxide film and the crystallite size of Fe3O4 constituting the oxide film, an oxide film with excellent durability can be obtained, and the occurrence of hydrogen embrittlement failure can be suppressed. Based on this, a rolling bearing and a manufacturing method thereof that can improve the durability of the raceway surface and rolling elements can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a cross-sectional view showing a rolling bearing according to an embodiment of the present invention.
[0034] Figure 2 It is a cross-sectional view schematically showing a damage testing device.
[0035] Figure 3 This is a graph showing the effect of the crystallite size on the scratch resistance, with the vertical axis representing the initial film thickness (μm) and the damaged film thickness (μm) of the black-dyed film and the horizontal axis representing the crystallite size (nm).
[0036] Figure 4 This is a graph showing the influence of the crystallite size on the scratch resistance when the vertical axis represents the damaged film thickness (μm) of the black-dyed film and the horizontal axis represents the crystallite size (nm) by an approximate straight line.
[0037] Figure 5This is a graph showing the relationship between the film formation rate and the crystallite size of Fe3O4 when the vertical axis is the film formation rate (μm / min) of the black dyed film and the horizontal axis is the crystallite size (nm) by an approximate straight line.
[0038] Figure 6 This is a graph showing the effect of film thickness on scratch resistance, with the vertical axis representing the initial film thickness (μm) of the black-dyed film and the damaged film thickness (μm) and the horizontal axis representing the initial film thickness (μm) of the black-dyed film.
[0039] Figure 7 This is a graph showing the influence of the initial film thickness on the scratch resistance, with the vertical axis representing the average damage rate (%) and the horizontal axis representing the initial film thickness (μm).
[0040] Fig. 8A This is a photograph in lieu of a drawing showing a peeling state when the initial film thickness of the black dyed film is 0.42 μm.
[0041] Figure 8B This is a photograph in lieu of a drawing showing a peeling state when the initial film thickness of the black dyed film is 0.84 μm.
[0042] Figure 8C This is a photograph in lieu of a drawing showing a peeling state when the initial film thickness of the black dyed film is 1.83 μm.
[0043] Fig.8D This is a photograph in lieu of a drawing showing a peeling state when the initial film thickness of the black dyed film is 1.97 μm.
[0044] Fig. 9 This is a graph showing the effect of the initial film thickness on film destruction using an approximate straight line, with the vertical axis representing the average peeling distance (μm) and the horizontal axis representing the initial film thickness (μm) of the black dyed film.
[0045] Fig.10 This is a graph showing the relationship between the initial film thickness and the crystallite size in each sample, with the vertical axis representing the initial film thickness (μm) and the horizontal axis representing the crystallite size (nm).
[0046] Fig.11 This is a graph showing the average damage rate (%) of each sample, with the vertical axis representing the average damage rate (%) and the horizontal axis representing the sample No.
[0047] Fig.12 This is a graph showing the relationship between the initial film thickness and the film formation rate in each sample, with the vertical axis representing the initial film thickness (μm) and the horizontal axis representing the film formation rate (μm / min). DETAILED DESCRIPTION
[0048] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the embodiments described below.
[0049] [Rolling bearings]
[0050] Figure 1 1 is a cross-sectional view showing a rolling bearing according to an embodiment of the present invention. In this embodiment, a thrust bearing is described as a rolling bearing, for example.
[0051] like Figure 1 As shown, the thrust bearing 10 includes: a first raceway ring 11 having a first raceway surface 13; a second raceway ring 12 having a second raceway surface 14; and a plurality of rolling elements 15 held freely in rolling relation between the first raceway surface 13 and the second raceway surface 14. In addition, a retainer 16 for holding the plurality of rolling elements 15 at predetermined intervals is disposed between the first raceway surface 13 and the second raceway surface 14.
[0052] In addition, Figure 1 In the present embodiment shown, an oxide film 17 containing Fe3O4 is formed on the first raceway surface 13 and the second raceway surface 14, respectively. Furthermore, the film thickness of the oxide film 17 and the crystallite size of Fe3O4 constituting the oxide film 17 are appropriately controlled. The oxide film 17 is generally formed by a treatment method called "blackening treatment", so the treatment for forming the oxide film 17 is sometimes referred to as "blackening treatment" and the oxide film 17 is referred to as "blackening film" hereinafter. In addition, hereinafter, "the crystallite size of Fe3O4" means the crystallite size calculated from the peak belonging to the (311) plane of Fe3O4.
[0053] It should be noted that the rolling bearing of the present embodiment needs to form an oxide film 17 containing Fe3O4 on the surface of a predetermined region of the thrust bearing 10 (specifically, at least one of the first raceway surface 13, the second raceway surface 14, and the rolling element 15). As a result, the generation of hydrogen from the first raceway surface 13, the second raceway surface 14, and the rolling element 15 constituting the thrust bearing 10 can be suppressed, and the generation of hydrogen embrittlement can be suppressed. In addition, since the film thickness of the oxide film 17 and the crystallite size of Fe3O4 constituting the oxide film 17 are appropriately controlled, the durability of the oxide film 17 can be improved, and the durability of the first raceway surface 13, the second raceway surface 14, and the rolling element 15 can be improved.
[0054] Next, conditions for improving the durability of the black-dyed film will be described below.
[0055] In order to improve the durability of the oxide film, it is important to suppress both the above-mentioned "coating wear" and "coating damage". Additionally, the microcrystalline size of Fe3O4 affects "coating wear". Furthermore, the microcrystalline size is affected by the film formation rate and depends on the treatment temperature of the blackening treatment, the treatment solution, and the type of steel on which the blackening treatment is performed. On the other hand, the residual stress affects "coating damage", and this is influenced by the film thickness of the blackening film. Furthermore, the film thickness is affected by the treatment time and the film formation rate of the blackening treatment.
[0056] It should be noted that in the judgment of durability, it is difficult to measure "wear resistance" and "damage resistance" completely separately, so the two are collectively referred to as "damage resistance".
[0057] <Relationship between the microcrystalline size of Fe3O4 and damage resistance>
[0058] Hereinafter, the results and discussions of Experiment 1 and Experiment 2 conducted to study the relationship between the microcrystalline size of Fe3O4 and damage resistance will be described.
[0059] (Experiment 1: Influence of microcrystalline size on damage resistance)
[0060] The film thickness of the oxide film formed by the blackening treatment was made approximately constant, and the film formation rate was varied in various ways to change the microcrystalline size, and the influence on the damage resistance of the blackening film was studied. The microcrystalline size was measured by X-ray diffraction (XRD: X-ray Diffraction) using cobalt (Co) as the radiation source for the oxide film formed by the blackening treatment, and was calculated using the Scherrer equation based on the peak attributed to the (311) plane of Fe3O4.
[0061] First, a blackening film was formed on the surfaces of the first raceway surface 13 and the second raceway surface 14 of the thrust bearing 10 made of SUJ2 steel specified in JIS G 4805:2019. Specifically, the first raceway ring 11 and the second raceway ring 12, which are the objects for forming the blackening film, were immersed in a treatment solution mainly composed of sodium hydroxide (NaOH) to form a blackening film containing Fe3O4.
[0062] It should be noted that in Experiment 1, the same treatment solution was used, and immersion treatments were performed under various treatment conditions to set various microcrystalline sizes.
[0063] Then, a damage test of the blackening film was carried out using a damage test device, and the film thickness before the test (initial film thickness) and the film thickness after the test were measured, and the damaged film thickness was calculated based on the difference therebetween.
[0064] Figure 2The damage test device 20 includes a container-shaped support table 21 with an open top, a rotating shaft 22 for rotating the thrust bearing 10, and a rotating disk 24 fixed to the rotating shaft 22. Lubricating oil 23 is injected into the support table 21.
[0065] During the damage test, the thrust bearing 10 is arranged between the inner bottom surface of the support table 21 and the rotating disk 24, the second raceway 12 of the thrust bearing 10 is fixed to the inner bottom surface of the support table 21, and the first raceway 11 is fixed to the rotating disk 24. Then, the thrust bearing 10 is rotated at a predetermined rotation speed while applying pressure through the rotating shaft 22 via the rotating disk 24, and the film thickness of the dyed black film after the test is measured.
[0066] Figure 3 This is a graph showing the effect of the crystallite size on the scratch resistance, with the vertical axis representing the initial film thickness (μm) and the damaged film thickness (μm) of the black-dyed film and the horizontal axis representing the crystallite size (nm).
[0067] in addition, Figure 4 This is a graph showing the influence of the crystallite size on the scratch resistance when the vertical axis represents the damaged film thickness (μm) of the black-dyed film and the horizontal axis represents the crystallite size (nm) by an approximate straight line.
[0068] The initial film thickness was 0.83 μm to 0.96 μm, and the crystallite sizes were four points: 2.73 nm, 2.85 nm, 3.08 nm, and 3.47 nm.
[0069] like Figure 3 As shown, when the film thickness is set to 0.9±0.1 μm and is substantially the same, the larger the crystallite size, the greater the damaged film thickness.
[0070] In addition, if Figure 4 As shown in FIG. 1 , the crystallite size is proportional to the damaged film thickness. From these results, it can be seen that when the film thickness is the same, the smaller the crystallite size, the better the damage resistance.
[0071] (Experiment 2: Effect of film forming speed on damage resistance)
[0072] Next, the effect of film formation rate was examined for thrust bearings with crystallite sizes of 2.73 nm, 2.85 nm, 3.08 nm, and 3.47 nm in the thrust bearings produced in Experiment 1. The film formation rate is the film thickness of the oxide film generated per unit time (μm / minute).
[0073] Figure 5The graph is a graph showing the relationship between the film forming rate (μm / min) of the black film and the crystallite size (nm) of the Fe3O4 when the vertical axis is the film forming rate of the black film and the horizontal axis is the crystallite size (nm) as an approximate straight line. It should be noted that the crystallite size was calculated using the Scherrer formula based on the peak attributable to the (311) plane of Fe3O4 measured by the X-ray diffraction method using cobalt (Co) as the radiation source in the same manner as in Experiment 1.
[0074] like Figure 5 As shown, it is confirmed that the crystallite size of Fe3O4 during black dyeing is proportional to the film forming speed. In addition, as mentioned above, the crystallite size is proportional to the film forming speed, and the crystallite size is proportional to the damaged film thickness, so the lower the film forming speed, the smaller the crystallite size, and the better the damage resistance.
[0075] The above-mentioned Experiments 1 and 2 mainly studied the factors affecting "film wear". In contrast, the following Experiment 3 mainly studied the factors affecting "film destruction".
[0076] <Relationship between film thickness and scratch resistance of black dyed film>
[0077] Next, the results and considerations of Experiments 3 and 4 conducted to examine the relationship between the film thickness of the black-dyed film and the scratch resistance will be described.
[0078] (Experiment 3: Effect of the thickness of the black-dyed film on the damage resistance)
[0079] In the black dyeing treatment, the same treatment liquid and treatment conditions were used to keep the film forming speed constant, thereby fixing the crystallite size, and the treatment time was varied to change the film thickness, and the influence on the scratch resistance was studied.
[0080] First, a dyed black film was formed on the surfaces of the first raceway surface 13 and the second raceway surface 14 of the thrust bearing 10 by the same method as in Experiment 1. The crystallite size was set to 3±0.04 nm, and the same damage test as in Experiment 1 was performed on the thrust bearings 10 obtained with various film thicknesses.
[0081] Figure 6 This is a graph showing the effect of film thickness on scratch resistance, with the vertical axis representing the initial film thickness (μm) of the black-dyed film and the damaged film thickness (μm) and the horizontal axis representing the initial film thickness (μm) of the black-dyed film.
[0082] in addition, Figure 7 This is a graph showing the influence of the initial film thickness on the scratch resistance, with the vertical axis representing the average damage rate (%) and the horizontal axis representing the initial film thickness (μm).
[0083] In Experiment 3, the same treatment solution was used for the blackening process and the film forming speed was kept constant, so the film quality, that is, the crystallite size of Fe3O4, was roughly the same. In addition, the average damage rate refers to the value calculated based on [average damaged film thickness at multiple locations / initial film thickness].
[0084] like Figure 6 and Figure 7 As shown, when the crystallite size of Fe3O4 is made substantially the same, the one with a thinner initial film thickness of the black dyed film has better scratch resistance.
[0085] (Experiment 4: Effect of the thickness of the black film on the resistance to film damage)
[0086] The film thickness of the black-dyed film is changed in various ways to study the effect on damage resistance, especially film destruction. Specifically, first, a thrust bearing 10 having a black-dyed film of various film thicknesses is produced by the same method as in the above-mentioned experiment 3. Next, five indentations are formed on the surface of the black-dyed film using the load and indenter specified in the Rockwell hardness test scale C (HRC). Then, the black-dyed film around the indentation is observed, and the distance from the outermost peripheral edge of each indentation to the peeling area of the black-dyed film (peeling distance) is measured. It should be noted that the peeling distance is measured at four locations for each of the five indentations, and the average value is calculated.
[0087] Figures 8A to 8D It is a photographic substitute for the accompanying drawing showing the peeling state of the black dyed film at each initial film thickness. Fig. 8A The initial film thickness is 0.42 μm. Figure 8B The initial film thickness is 0.84 μm. Figure 8C The initial film thickness is 1.83 μm. Fig.8D The initial film thickness is 1.97 μm. An example of the peeling distance is indicated by an arrow in the figure.
[0088] in addition, Fig. 9 This is a graph showing the effect of the initial film thickness on film destruction when the vertical axis represents the average peeling distance (μm) and the horizontal axis represents the initial film thickness (μm) of the black dyed film using an approximate straight line.
[0089] like Figures 8A to 8D and Fig. 9 As shown, it can be seen that there is a proportional relationship between the initial film thickness of the dyed black film and the average peeling distance. In addition, the dyed black film is a film obtained by oxidizing Fe to form Fe3O4, and volume expansion occurs when Fe3O4 is formed. Therefore, the dyed black film has residual stress. The thicker the dyed black film, the greater the volume expansion and the greater the residual stress. Figures 8A to 8D and Fig. 9 The peeling distance shown is considered to be affected by the residual stress of the above-mentioned black dyed film, and it is shown that the thinner the initial film thickness is, the better the film damage resistance is.
[0090] Based on the observations made in Experiments 1 to 4, the preferred ranges of the film thickness and the Fe3O4 crystallite size that can improve the scratch resistance of the black-dyed film were obtained. The reasons for these limitations are described below.
[0091] [Thickness of black dyed film: 0.6 μm or more and 2.0 μm or less]
[0092] The thickness of the black film particularly affects the film damage resistance. If the film thickness is less than 0.6 μm, the black film becomes too thin, the life against damage becomes short, and the effect of suppressing hydrogen generation reaction becomes small. Therefore, the film thickness of the black film is preferably 0.6 μm or more.
[0093] On the other hand, if the film thickness exceeds 2.0 μm, the black film is easily damaged and the durability is reduced. Therefore, the film thickness of the black film is 2.0 μm or less, preferably 1.5 μm or less, more preferably 1.2 μm or less, and further preferably 0.8 μm or less.
[0094] [Fe3O4 crystallite size: 2.5 nm or more and 3.2 nm or less]
[0095] The crystallite size of Fe3O4 particularly affects the wear resistance of the coating. The crystallite size of Fe3O4 is greatly affected by the film forming speed. Therefore, if the crystallite size of Fe3O4 is to be less than 2.5nm, the time used for film forming is too long, and the productivity is reduced. Therefore, the crystallite size of Fe3O4 is greater than 2.5nm, preferably greater than 2.7nm.
[0096] On the other hand, if the crystallite size of Fe3O4 exceeds 3.2 nm, the desired scratch resistance of the black dyed film cannot be obtained. Therefore, the crystallite size of Fe3O4 is 3.2 nm or less, preferably 3.0 nm or less, and more preferably 2.9 nm or less.
[0097] In the above embodiment, the example using the thrust bearing 10 is shown as the rolling bearing on which the black film (oxide film 17) is formed. However, the present invention is not limited to the thrust bearing 10, and can also be applied to a radial bearing, for example.
[0098] In addition, the area where the oxide film 17 is formed is not limited to the raceway surface (first raceway surface 13, second raceway surface 14) side as described in the above embodiment, and can also be formed on the surface side of the rolling element 15, and can also be formed on both sides. However, in order to more effectively suppress the occurrence of hydrogen embrittlement damage, the oxide film 17 is preferably formed on both the first raceway surface 13 and the second raceway surface 14, and the surface of the rolling element 15. In addition, the rolling element 15 can be a ball or a roller. Furthermore, the number of treatments in the blackening process can be only one time or multiple times.
[0099] Furthermore, in the above-mentioned embodiment, an example using SUJ2 steel is shown, but the present invention is not limited to SUJ2 steel, and any steel that can be dyed black can be applied.
[0100] [Manufacturing method of rolling bearing]
[0101] The method for manufacturing a rolling bearing of the present embodiment is a method for manufacturing the above-mentioned rolling bearing, and includes a step of forming a black film (oxide film 17) containing Fe3O4 on at least one of the surfaces of the above-mentioned first raceway surface 13 and the second raceway surface 14, and the rolling element 15. The conditions in the method for manufacturing a rolling bearing of the present embodiment are described below.
[0102] [Film formation rate of black dyed film: 0.003 μm / min or more and 0.034 μm / min or less]
[0103] As mentioned above, the film-forming speed of the black film has a great influence on the crystallite size of Fe3O4. When the crystallite size of Fe3O4 is small, the damage resistance is excellent, but when the film-forming speed is lower than 0.003μm / min, the productivity decreases. Therefore, the film-forming speed of the black film is 0.003μm / min or more.
[0104] On the other hand, if the film formation rate of the black film exceeds 0.034 μm / min, the crystallite size of Fe3O4 exceeds 3.2 nm, and the desired scratch resistance cannot be obtained. Therefore, the film formation rate of the oxide film is 0.034 μm / min or less, preferably 0.026 μm / min or less.
[0105] Example
[0106] Made of SUJ2 steel specified in JIS G 4805:2019 Figure 1 In the thrust bearing 10 shown, the thrust retaining ring constituting the first raceway surface 13 and the second raceway surface 14 is dyed black under various treatment conditions to form an oxide film 17 containing Fe3O4 having various crystallite sizes.
[0107] It should be noted that the crystallite size of Fe3O4 is appropriately adjusted by controlling the film formation rate of the oxide film 17. The thrust bearing 10 has an inner diameter of 25 mm, an outer diameter of 52 mm, and a width of 18 mm, and uses six rolling elements 15 with a diameter of 3 / 8 inches.
[0108] The treatment conditions, film forming speed and crystallite size of Fe3O4 for the blackening treatment are shown in Table 1 below. The treatment liquids A, B and C in Table 1 below are treatment liquids with NaOH as the main component and different compositions, and are generally used as treatment liquids for blackening treatment. In addition, sample No. (2) was subjected to blackening treatment twice at different treatment speeds for 30 minutes each in accordance with DIN 50938: 2018-01. The other samples were subjected to blackening treatment once.
[0109] The crystallite size was measured by the same method as in Experiment 1.
[0110] Next, the initial film thickness of the black film was measured for the thrust bearings 10 of the obtained samples No. (1) to (11), and then Figure 2 The damage test apparatus 20 shown was used to perform the damage test of the black-dyed film three times (n=3) under each condition. The damage test apparatus 20 was rotated at the following rotation speed for 5 days while applying pressure to the thrust bearing 10 .
[0111] The specific conditions of the damage test are as follows: It should be noted that the "stress cycle number" shown below means the number of times the rolling element passes through a predetermined position in the raceway ring.
[0112] Surface pressure: 2.2 (GPa)
[0113] Viscosity of lubricating oil (ISO viscosity grade number): VG 68
[0114] Rotation speed: 1000(rpm)
[0115] Stress cycle number: 2.16×10 7 (Second-rate)
[0116] After the damage test, the thrust ring of each sample was cut off, and the remaining black film (remaining film thickness) was measured at 4 locations using a scanning electron microscope (SEM). It should be noted that the film thickness of the black film in the area where the rolling element is not in contact is taken as the initial film thickness (μm), the value obtained by subtracting the residual film thickness at each point from the initial film thickness and averaging the values is taken as the average damaged film thickness (μm), and the value obtained by dividing the average damaged film thickness by the initial film thickness and multiplying by 100 is taken as the average damage rate (%). The initial film thickness and the results of the damage test are shown together in the following Table 1.
[0117] [Table 1]
[0118] Table 1
[0119]
[0120] Fig.10This is a graph showing the relationship between the initial film thickness and the crystallite size of each sample when the vertical axis is the initial film thickness (μm) and the horizontal axis is the crystallite size (nm). Fig.11 This is a graph showing the average damage rate (%) of each sample when the vertical axis is the average damage rate (%) and the horizontal axis is the sample No. Fig.12 This is a graph showing the relationship between the initial film thickness and the film formation rate in each sample, with the vertical axis representing the initial film thickness (μm) and the horizontal axis representing the film formation rate (μm / min).
[0121] As shown in Table 1, Figure 10 to Figure 12 As shown, since the film thickness (initial film thickness) of the dyed black film of sample No. (8) exceeds the upper limit of the range of the present invention, the average damage rate is 100%, indicating that a dyed black film with poor durability is formed. In addition, since the crystallite size of the dyed black film of sample No. (9) to (11) exceeds the upper limit of the range of the present invention, the average damage rate is 100%, indicating that a dyed black film with poor durability is formed.
[0122] On the other hand, for Samples No. (1) to (7), the film forming speed was appropriately controlled, and a black film having a desired initial film thickness of 0.6 μm or more and 2.0 μm or less was formed, so that the crystallite size of Fe3O4 was 2.5 nm or more and 3.2 nm or less. Therefore, for Samples No. (1) to (7), regardless of the treatment liquid and the number of treatments, the black film remained even after the severe damage test, and a black film with good durability was obtained. In addition, the time required for film formation was not too long, and the productivity was good.
[0123] In particular, Fig.10 As shown, the initial film thickness of samples No. (1) to (3), (5) and (7) is less than 1.2 μm, which is the more preferred upper limit of the present invention, and the crystallite size is more than 2.5 nm and less than 3.2 nm, so the average damage rate is less than 65%, and a black dyed film with excellent durability can be obtained. In addition, sample No. (7) has the smallest crystallite size, so compared with sample No. (1) to (6), the time required for film formation is increased, but the average damage rate is the lowest and the durability is excellent.
[0124] In addition, if Fig.12As shown, in samples No. (1) to (3), (5) and (7), the film forming rate was controlled to 0.003 μm / min to 0.034 μm / min, and the black film was formed in such a manner that the initial film thickness was within the more preferred range of the present invention, that is, 1.2 μm or less, so the average damage rate was 65% or less, and a black film with excellent durability could be obtained. In particular, the black film was formed in such a manner that the film forming rate was within the preferred range, that is, 0.026 μm / min or less, and the initial film thickness was within the particularly preferred range, that is, 0.8 μm or less, so the average damage rate was 40% or less, and it was confirmed that the durability was further improved.
[0125] Above, various embodiments have been described with reference to the accompanying drawings, but the present invention is certainly not limited to this example. Those skilled in the art will appreciate that various modifications or amendments can be made within the scope of the claimed content, and these modifications or amendments certainly belong to the technical scope of the present invention. In addition, the various constituent elements in the above-mentioned embodiments may be arbitrarily combined without departing from the scope of the gist of the present invention.
[0126] In addition, this application is based on the Japanese patent application (Japanese Patent Application No. 2022-111257) filed on July 11, 2022, and the contents are incorporated herein by reference.
[0127] Explanation of symbols
[0128] 10 Thrust bearing
[0129] 11 First raceway
[0130] 12 Second raceway
[0131] 13 First raceway surface
[0132] 14 Second raceway surface
[0133] 15 Rolling element
[0134] 16 Retainer
[0135] 17 Fe3O4-containing oxide film
[0136] 20 Damage test device
[0137] 21 Supporting platform
[0138] 22 Rotation axis
[0139] 23 Lubricating oil
[0140] 24 Rotating disk
Claims
1. A rolling bearing, characterized in that: The invention comprises: a first raceway ring having a first raceway surface; a second raceway ring having a second raceway surface; and a plurality of rolling elements held between the first raceway surface and the second raceway surface in a freely rolling manner. At least one of the first raceway surface, the second raceway surface, and the surface of the rolling element has an oxide film containing Fe3O4, The oxide film has a thickness of 0.6 μm or more and 2.0 μm or less. The crystallite size calculated from the peak attributed to the (311) plane of Fe3O4 is greater than or equal to 2.5 nm and less than or equal to 3.2 nm.
2. The rolling bearing according to claim 1, characterized in that: The oxide film is formed on the surfaces of the first and second raceway surfaces and the surface of the rolling element.
3. A method for manufacturing a rolling bearing, characterized in that: A method for manufacturing a rolling bearing according to claim 1 or 2, The manufacturing method includes the step of forming an oxide film containing Fe3O4 on at least one of the first raceway surface, the second raceway surface, and the surface of the rolling element. The film formation rate of the oxide film is set to 0.003 μm / min or more and 0.034 μm / min or less.
Citation Information
Patent Citations
Rolling component and rolling bearing
JP2019039523A
Rolling bearing
JP2019113126A
gaming machines
JP2022111257A
Cited By
Method for prolonging service life of bearing by forming oxide layer on surface of metal bearing
CN121380959A